Design and Analysis of Agroforestry Experiments: An Overview - Jaggi, Seema; Gupta, V.K.; Sharma, V.K. (Indian Journal of Agroforestry, 2020)
The purpose of this paper is to give an overview of some of the designs used in agroforestry experimentation along with the layout plans, where-ever possible. The analytical techniques that are being used in agroforestry experiments have also been discussed and some other techniques that can be possibly used have been indicated.